Scaphosepalum Pfitzer - Karremans Lok, Adam Philip (2022)
There are just over 50 species of Scaphosepalum Pfitzer recog- nized today. They are widely distributed from Mexico to Bolivia and the Guyana Shield, with the highest species diversity found in the northern Andes, especially Colombia and Ecuador. They are notoriously absent from the Antilles and Brazil.